Midtarsal joint sprain - a quick review - Kwiatkowski, Filip; Popiela, Dariusz; Urbańska, Karina; Stojak, Łukasz; Baczewski, Mateusz; Grego, Mateusz; Grego, Katarzyna; Czyż, Witold (Quality in Sport, 2025)
A midtarsal joint sprain (MJS) is a relatively common underdiagnosed injury that can be confused with an ankle sprain. Usually the only way to avoid misdiagnosis is to have imaging performed by an experienced sonographer or radiologist, but in reality it is mainly due to a lack of knowledge of how to differentiate between these two injuries. This review focuses on a brief overview of MJS to help you better understand when to consider the possibility of this injury, how to investigate it, and how to treat it.